THE INFLUENCE OF STUDENT EXPERIENCE TOWARD STUDENT SATISFACTION: IN CASE OF SBM ITB - Dewi, Laras Anjarsari; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract. As globalization rise the competitions of education field become quiet competitive. The improvement of the learning program always becomes a competition between university and institution. Where student satisfaction commonly used to evaluate the service program in higher education. The evaluation later will be used to develop their program. As the program is designed there are several aspects that need to be considered. One of them is quality assurance. The quality assurance is applied on the learning design that later become part of student experience. The objective of this research is to measure the influence of student experience toward student satisfaction.The data collected using questionnaire. The sample method used in this research is random sampling method and Slovin’s formula to calculate the amount of sample need. As the result 296 data of respondent is collected, the data then analyzed using classical assumption and simple linear regression. To measure the influence of independent variables (student experience measured by quality assurance attribute) to the dependent variable (student satisfaction).The result shown that student satisfaction is 30.8% influenced by the student experience. Furthermore, each of quality assurance attribute has positive relationship with the student satisfaction. This study also finds that the designed grading policy has big influence toward the student satisfaction and also the only attribute that can influence other three attribute. This finding can be a reason for SBM ITB to give more attention on designing quality assurance in order to increase the student satisfaction.Keyword: Education, Student experience, Student satisfaction, Quality assurance, Quantitative research.